The prevalence and associated factors of alcohol use among pregnant women attending antenatal care at public hospitals Addis Ababa, Ethiopia, 2019 - Getaneh Tesfaye; Demeke Demlew; Meseret G/tsadik; Fikreselam Habte; Gebeyaw Molla; Yohannes Kifle; Gebreslassie Gebreegziabher (BMC Psychiatry, 2020)
Abstract Background Alcohol use during pregnancy is a significant public health problem, ultimately affecting the neonatal offspring. Recent studies explore that no safe amount and safe time to drink alcohol during pregnancy. Even though drinking in pregnancy has a wide range of problems, a small number of scientific publications document on the magnitude of drinking alcohol during pregnancy in Sub-Saharan African countries including Ethiopia. The aim of this study was to assess prevalence and associated factors of alcohol use among pregnant women attending prenatal care at public hospitals, Addis Ababa, Ethiopia. Methods Hospital based cross sectional study was employed from May 7 to June 6, 2019 at public hospitals, Addis Ababa. A total of 585 pregnant women participated in the study selected through systematic random sampling technique. Frequency of consumption was measured by using AUDIT. Frequency tables and graphs were used to describe the study variable. The association between variables analyzed with bi-variable and multivariable binary logistic regression. A statistical significance was declared at p value < 0.05 with 95% confidence interval. Result A total of 585 participants were included in the study with the response rate of 98.6%. The study showed that the prevalence of alcohol use among pregnant women were 37.1% with (95% CI, 33.2–41). Factors like no formal education [AOR = 3.22, 95%CI, 1.72, 6.02], pre-pregnancy alcohol use [AOR = 3.16, 95%CI, 2.03, 4.91], partner alcohol use [AOR = 3.43, 95%CI, 2.21, 5.32], and poor social support [AOR = 3.16, 95%CI, 1.88, 5.31] were statistically associated with alcohol use during pregnancy. Conclusion In this study the prevalence of alcohol use during pregnancy was high as compared to majority of other studies. This study observed that no formal education, pre-pregnancy alcohol use, partner alcohol use, and poor social support, were highly associated with alcohol use during pregnancy. Based on the findings of this study early management of alcohol use and problematic alcohol use is needed for pregnant women.